(untitled) (International Journal of Food and Nutritional Sciences, 2021)
gurjit.dbtram.b4@gmail.com, rajivkr2020@gmail.com Abstract: The rising emphasis on health and wellness has prompted a need for hotels to offer nutritious dining options. This pilot study develops a nutritional assessment framework for hotel menus to enhance the nutritional quality of hotel offerings and cater to health-conscious guests. The framework is designed to provide a structured approach for evaluating menu items based on established nutritional guidelines. The study employs a mixed-methods approach, including expert consultations, menu evaluations, and pilot testing in selected hotels. The results identify key components of the framework, such as nutritional guidelines, menu analysis tools, and training modules for hotel staff. The pilot testing phase demonstrates the feasibility of the framework, highlighting benefits like increased awareness of nutritional issues and challenges such as resource constraints and staff training needs. This research contributes to filling a gap in the hospitality industry by offering a practical tool for improving menu nutrition. The study’s findings provide a foundation for further research and practical applications, aiming to align hotel dining experiences with contemporary health and wellness trends.